Hikmah Covid-19 (II): Inspirasi Dialektika Negatif Adorno dan Vandana Shiva - Dr. Y. Slamet Purwadi (Fakultas Filsafat, 2020)
Hikmah Covid-19 (II): Inspirasi Dialektika Negatif Adorno dan Vandana Shiva